(untitled) (REMUNOM, 2025)
This article is a literature review, with the aim of emphasizing the effects of Botulinum Toxin associated with physiotherapeutic treatments in patients with spastic cerebral palsy. CP is attributed to a group of non-progressive disorders resulting from damage to the maturing brain, and described as a set of postural and movement disorders that end up leading to functional limitations in the child. Botulinum Toxin A is a potent neurotoxin produced by the anaerobic bacterium Clostridium Botulinum, and is indicated in cases of spasticity, which is defined as stiffness and involuntary contractions of muscles, making movement difficult. For the development of this study, it was decided to carry out a bibliographical research based on a review of scientific literature. SCIELO (Scientific Electronic Library Online), Google Scholar, LILACS (Latin American and Caribbean Health Sciences Literature) were used as the research database.